ANALYSIS OF EFFECTIVENESS OF ANTIBIOTICS IN RECURRENT TYPES OF ERYSIPELAS DISEASE IN SAMARKAND REGION - Uzakova Gavkhar Zakirovna; Shodiyeva Dilafruz Abdujalolovna (Лучшие интеллектуальные исследования, 2024)
INTRODUCTION. In recent years, in the clinical course of leprosy, severe forms with the predominance of intoxication syndrome have been observed, the number of complications has increased, and the younger generation of erysipelas has been observed. according to the analysis, the number of patients with bullous and hemorrhagic forms of erysipelas has been increasing in recent years. in recent years, cases of relapse of the disease have been frequent in patients (43,3%). antibacterial therapy is important in the etiopathogenetic approach to the treatment of erysipelas disease. the fact that the treatment regimens used in the treatment of erysipelas at the present time are insufficient both for the regression of the clinical symptoms in the acute period of the disease and for the prevention of its recurrence has prompted researchers to look for new methods of treatment, including the use of broad-spectrum antibiotics in combination with immunocorrectors in the treatment of the disease. nowadays, it is important to study the characteristics of the development of erysipelas, to improve the efficiency of treatment of patients, to improve diagnostic methods, to prevent the recurrence of the disease, and scientific and practical researches are important.